Energy intensity of water supply by pumping stations during reconstruction of irrigated sites using low-pressure sprinkling machines - Nikolay F. Ryzhko; Fyrid K. Abdrazakov; Sergey N. Ryzhko; Evgeny S. Smirnov; Evgeny A. Shishenin; Sergey A. Horin (Мелиорация и гидротехника)
Purpose: to assess the energy intensity of water supply by pumping stations during partial and complete reconstruction of an irrigated area, to refine the methodology for calculating the optimal energy intensity of water supply by a pumping station to improve irrigation efficiency. Materials and methods. To assess the efficiency of irrigation and the energy intensity of irrigation during reconstruction, it is necessary to carry out hydraulic and energy calculations. The methodology for assessing the energy intensity of water supply by a pumping station has been refined, which made it possible to determine the areas for improving irrigated sites. Results. The analysis of irrigated areas in Saratov region showed that three main groups can be distinguished. The first one includes irrigated areas where reconstruction was not carried out and high-pressure pumps and Fregat sprinkler machines are used. For supplying 1000 cub. m of water here, significant amounts of energy are spent – 475–668 kW•h, it is often impossible to include the design number of operating machines simultaneously. The second group includes irrigated sites with partial reconstruction, where high-pressure pumps are used and the machines have been modernized for low-pressure operation or replaced with low-pressure electrified machines. In this case, irrigation costs are reduced to 266–510 kW•h, i. e. by 1.1–2.2 times. The third group includes irrigated areas where a complete reconstruction has been carried out with the introduction of energy-saving pumps and low-pressure machines, and irrigation costs have been reduced to 174–210 kW•h, i.e. by 1.8–3.2 times. But even in such irrigated areas, errors in design and operation were revealed. Conclusions. To reduce energy costs for irrigation, it is necessary to carry out a complete reconstruction of irrigated areas with the introduction of low-pressure sprinkler machines and energy-saving and variable pumps, as well as to ensure their operation in the optimal mode. Calculations using an improved method for assessing the energy intensity of irrigation will allow you to select the optimal parameters of pumps, sprinkler machines and pipes of a closed irrigation network.